2011
DOI: 10.5267/j.ijiec.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Multi products single machine economic production quantity model with multiple batch size

Abstract: In this paper, a multi products single machine economic production quantity model with discrete delivery is developed. A unique cycle length is considered for all produced items with an assumption that all products are manufactured on a single machine with a limited capacity. The proposed model considers different items such as production, setup, holding, and transportation costs. The resulted model is formulated as a mixed integer nonlinear programming model. Harmony search algorithm, extended cutting plane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…This paper also proposed scientific techniques for handling human decision problem in the university system. Our literature search revealed several methods for solving MCDM problems, but some are cost minization based e.g., inventory based methods, volume discount, mathematical progrmming techniques, GA (Teimoury et al,2011, Mak and Cui, 2011, Mogri et al, 2010, Saen, 2010, Taleizadeh et al, 2011, and Woarawichai et al, 2010. And cost as a quantitative criterion is not a sufficient attribute for addressing contemporary selection problems…”
Section: Resultsmentioning
confidence: 99%
“…This paper also proposed scientific techniques for handling human decision problem in the university system. Our literature search revealed several methods for solving MCDM problems, but some are cost minization based e.g., inventory based methods, volume discount, mathematical progrmming techniques, GA (Teimoury et al,2011, Mak and Cui, 2011, Mogri et al, 2010, Saen, 2010, Taleizadeh et al, 2011, and Woarawichai et al, 2010. And cost as a quantitative criterion is not a sufficient attribute for addressing contemporary selection problems…”
Section: Resultsmentioning
confidence: 99%
“…Sana (2011) investigated an integrated production and inventory model for distributor, manufacturer and retailer in a supply chain with perfect and imperfect quality items. Taleizadeh et al (2011a) proposed an EOQ model for a multi-product inventory system in which those are produced on a single machine with a limited capacity. Taleizadeh et al (2011b) suggested an EPQ model for multi-product single-machine manufacturing systems with rework process and back-ordering.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Over the last four decades, an abundance of research on this topic has been undertaken and many interesting results have been reported in the literature, see, e.g., Aggarwal (1974), Clark (1972), Hadley and Whitin (1963), Nahmias (1982), Silver (1981), Tinarelli (1983), Veinott (1966), Wagner (1980), Whitin (1954), Taleizadeh et al, (2011) andHsu (2012). We know that four major assumptions in the classical EPQ model are that (i) demand is constant over time and known with certainty, (ii) no excess stock is carried, and no backorders and lost sales are allowed, (iii) the lead time is zero, and (iv) the unit production cost is independent of the production quantity.…”
Section: Reliability Adjusted Epq (Economic Production Quantity) Modelmentioning
confidence: 99%